No evidence of brown adipose tissue activation after 24 weeks of supervised exercise training in young sedentary adults in the ACTIBATE randomized controlled trial - Martinez-Tellez Borja; Sanchez-Delgado Guillermo; Acosta Francisco M.; Alcantara Juan M. A.; Amaro-Gahete Francisco J.; Martinez-Avila Wendy D.; Merchan-Ramirez Elisa; Muñoz-Hernandez Victoria; Osuna-Prieto Francisco J.; Jurado-Fasoli Lucas; Xu Huiwen; Ortiz-Alvarez Lourdes; et al. (Nature Portfolio, 2025)
Exercise modulates both brown adipose tissue (BAT) metabolism and white adipose tissue (WAT) browning in murine models. Whether this is true in humans, however, has remained unknown. An unblinded randomized controlled trial (ClinicalTrials.gov ID: NCT02365129) was therefore conducted to study the effects of a 24-week supervised exercise intervention, combining endurance and resistance training, on BAT volume and activity (primary outcome). The study was carried out in the Sport and Health University Research Institute and the Virgen de las Nieves University Hospital of the University of Granada (Spain). One hundred and forty-five young sedentary adults were assigned to either (i) a control group (no exercise, n = 54), (ii) a moderate intensity exercise group (MOD-EX, n = 48), or (iii) a vigorous intensity exercise group (VIG-EX n = 43) by unrestricted randomization. No relevant adverse events were recorded. 97 participants (34 men, 63 women) were included in the final analysis (Control; n = 35, MOD-EX; n = 31, and VIG-EX; n = 31). We observed no changes in BAT volume (Delta Control: -22.2 +/- 52.6 ml; Delta MOD-EX: -15.5 +/- 62.1 ml, Delta VIG-EX: -6.8 +/- 66.4 ml; P = 0.771) or F-18-fluorodeoxyglucose uptake (SUVpeak Delta Control: -2.6 +/- 3.1 ml; Delta MOD-EX: -1.2 +/- 4.8, Delta VIG-EX: -2.2 +/- 5.1; p = 0.476) in either the control or the exercise groups. Thus, we did not find any evidence of an exercise-induced change on BAT volume or activity in young sedentary adults.Exercise modulates brown adipose tissue (BAT) metabolism in murine models. Here the authors report that there is no evidence that 24 weeks of supervised exercise training modulates BAT volume or function in young sedentary adults in the ACTIBATE randomized controlled trial.